Eugenia ochracea (Myrtaceae, Myrteae), a new species from Atlantic forest of Espírito Santo, Brazil - Valdemarin, Karinne Sampaio; Mazine, Fiorella F.; Souza, Vinicius Castro (Brittonia, 2019)
A new species of Eugenia sect. Umbellatae (Myrtaceae, Myrteae) from the Atlantic forest of Espírito Santo, Brazil is proposed: Eugenia ochracea . It is most similar to Eugenia crassa and Eugenia barrana , and the presence mainly of floccose indumentum on leaves and lanceolate to linear bracteoles allow us to propose it as new. Comments on its distribution and habitat, conservation assessment, and other morphologically similar species are herein presented.